PEMBERDAYAAN UMKM MELALUI STRATEGI PEMASARAN DAN PELATIHAN PRODUKSI ES PISANG IJO BAGI MASYARAKAT - Dony Novaliendry; Wahdatul Aulia; Adrian Rama Putra; Anita Ica Riskia; Dwi Ayu Aziza; Hulwa Zuhrahriani Hibatullah; Selma Eka Putri; Vega Lovita (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Micro, Small, and Medium Enterprises (MSMEs) play an important role in local economic development, yet they are often constrained by limited production skills and marketing strategies. This community service program aims to enhance MSME capabilities through training in making es pisang ijo and marketing strategies for the community of Jorong Ujung Padang, Nagari Tanjung. The activities were conducted using a descriptive qualitative approach with a Participatory Action Research (PAR) model. The stages of the program included socialization of MSME concepts and marketing strategies, practical training on making es pisang ijo (ingredient preparation, cooking, serving, and packaging), and promotion training through social media. The results showed that participants, particularly women and young women, were highly enthusiastic and actively engaged in discussions and practical activities. The program successfully improved participants’ knowledge and skills in producing es pisang ijo as well as their understanding of simple marketing strategies. The main conclusion of this program is that the community recognizes es pisang ijo as a promising business opportunity to increase household income and support local economic development, while also encouraging sustainable local potential–based economic independence that is adaptive to market demands. ABSTRAK UMKM berperan penting dalam pembangunan ekonomi lokal, namun sering terkendala oleh keterbatasan keterampilan produksi dan strategi pemasaran. Program pengabdian masyarakat ini bertujuan meningkatkan kapabilitas UMKM melalui pelatihan pembuatan es pisang ijo dan strategi pemasaran bagi masyarakat Jorong Ujung Padang, Nagari Tanjung. Kegiatan dilaksanakan dengan pendekatan kualitatif deskriptif menggunakan model Participatory Action Research (PAR). Tahapan kegiatan meliputi sosialisasi konsep UMKM dan strategi pemasaran, pelatihan praktik pembuatan es pisang ijo (persiapan bahan, pemasakan, penyajian, pengemasan), dan pelatihan promosi melalui media sosial. Hasil kegiatan menunjukkan peserta, khususnya perempuan dan remaja putri, sangat antusias dan aktif berpartisipasi dalam diskusi maupun praktik. Kegiatan berhasil meningkatkan pengetahuan dan keterampilan peserta dalam memproduksi es pisang ijo serta memahami strategi pemasaran sederhana. Kesimpulan utama dari kegiatan ini adalah masyarakat menyadari es pisang ijo sebagai peluang usaha yang menjanjikan untuk meningkatkan pendapatan rumah tangga dan mendukung pembangunan ekonomi lokal, serta mendorong kemandirian ekonomi berbasis potensi lokal yang berkelanjutan dan adaptif terhadap kebutuhan pasar.